The Effect of Compensation, Organizational Culture and Work Motivation on Turnover Intention: Pengaruh Kompensasi, Budaya Organisasi Dan Motivasi Kerja Terhadap Turnover Intention - Susanti, Feni Dwi; Rizal, Asat (Universitas Muhammadiyah Sidoarjo, 2022)
This research is a quantitative research. The purpose of this study was to determine the effect of compensation, organizational culture and work motivation on employee turnover intention. The sample used in this study were 85 respondents, namely all employees of CV. Indonesian Tex Star. The data analysis used was multiple linear regression analysis and hypothesis testing using t test and F test. The results showed that there was a partial and significant effect of compensation, organizational culture and work motivation variables on Turnover Intention on CV. Indonesian Tex Star. Meanwhile, simultaneously there is a significant effect of compensation variables, organizational culture and work motivation on Turnover Intention on CV. Star Tex Indonesia